Examination of visual search behaviors in a badminton serving task as a function of anxiety - Tang, Kirt Soon (2017)
The badminton serve is crucial to start a rally. A good low serve in a doubles game, is usually described as the shuttlecock flying just over the net and onto the service line. Executing it successfully allows the server to get the advantage of the rally by preventing the opponent from attacking first. The ability to perform well in the serving task is associated with the Quiet Eye (QE), which is the final fixation prior to the onset of movement. However, the presence of anxiety has previously been associated with poorer performance. Hence, the aim of this study was to examine the QE duration in two condition settings (low anxiety; high anxiety) using the badminton low serving task. 10 skilled (at least six years of structured practice and three years of competitive experience) badminton players were recruited to perform 10 trials of low serves each in both conditions in a counterbalanced manner and visual search behavior data were collected using the eye tracker glasses. The results displayed significantly shorter QE duration in high anxiety condition compared to the low anxiety condition. This implies that anxiety does affect the QE duration which in turn lead to poorer performance. With these findings, it provides insights which adds on to existing literature regarding QE duration and sport expertise. Further research may be done to investigate the areas of interest that could possibly be associated with anxiety and the QE.